Analisis Kecacatan Produk Fillet Skin On Red Mullet Dengan The Basic Seven Tools Of Quality Dan Usulan Perbaikannya Menggunakan Metode Fmea (Failure Modes And Effect Analysis) Pada PT. Holi Mina Jaya - Andi Trias Aryanto; Tuwanku Aria Auliandri (Universitas Airlangga, 2015)
Increasingly fierce competition make quality becomes a more value in the eyes of consumers. Keeping quality of being a need for companies to be able to stay in business. PT. Holi Mina Jaya is an Indonesian company that is engaged in marine fish processing. One of the flagship products offered are Fillet Skin On Red Mullet. The purpose of this study was to identify factors disability that occurs in the product Red Mullet Fillet Skin On analysis of the seven basic tools of quality and propose improvements to the failure modes and effects analysis (FMEA). The study focused on the stages of production that have a direct impact on the finished products includes receiving, filleting, and washing. This study uses five of the seven basic quality tools, which flow charts, check sheets, histograms, cause and effect diagram and Pareto charts to identify defects. For quality improvement proposals using FMEA method by finding the value of the RPN (Risk Priority Number), have described the RPN value calculation by multiplying the value of Severity, Occurrence and Detection. Highest cause of any kind of disability, like any form of meat are less scrupulous employees, and skilled with the value of RPN 120, not fresh fish product defects are less rigorous sorting process HR RPN value by 54, and the last meat is not clean of thorns is less scrupulous employees with RPN at 36.